2014
DOI: 10.3109/02652048.2014.913722
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of naproxen–ethyl cellulose microparticles by spray-drying technique and their application to textile materials

Abstract: The objective of this study is to develop a new textile-based drug delivery system containing naproxen (NAP) microparticles and to evaluate the potential of the system as the carrier of NAP for topical delivery. Microparticles were prepared by spray-drying using an aqueous ethyl cellulose dispersion. The drug content and entrapment efficiency, particle size and distribution, particle morphology and in vitro drug release characteristics of microparticles were optimized for the application of microparticles onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…For formulation with a drug:EC ratio of 1:4, about 10% of a drug was released after 5 min, and about 45% after 30 min. SEM photomicrographs revealed spherical, well-separated particles with a smooth surface and absence of agglomerates [36].…”
Section: Resultsmentioning
confidence: 99%
“…For formulation with a drug:EC ratio of 1:4, about 10% of a drug was released after 5 min, and about 45% after 30 min. SEM photomicrographs revealed spherical, well-separated particles with a smooth surface and absence of agglomerates [36].…”
Section: Resultsmentioning
confidence: 99%
“…Application of EC microparticles containing naproxen to textile materials was studied by Arici et al Microparticles were prepared by spray-drying using an aqueous EC dispersion and applied to orthopedic support materials. Since these materials are used for traumatic irritations, over-forced ligaments and tendons, and specific problems of various joints, it was concluded that they can serve as potential drug delivery systems [102].…”
Section: Applicability Of Ec In Pharmaceutical Formulationsmentioning
confidence: 99%
“…These morphological characteristics point out that the CHD is dispersed all over the MPs (Figure 1). In other spray-drying studies performed by using aqueous polymeric dispersions, MPs with similar morphological characteristics were also obtained (Rattes, 2007;Arici, 2014). …”
Section: Particle Morphologymentioning
confidence: 74%